AFRICA AND THE EMERGING POWERS: THE SOUTH AND THE UNHOLY COOPERATION - Visentini, Paulo (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
In the early 21st Century, after the second "lost decade" and rather surprisingly, Africa resumes economic growth, socioeconomic development, relatively political stability and progress in the processes of regional and continental integration. The reason for such inflection results from a combination of both internal and external factors: the stabilization of large African states, the performance of its leaders in the pursuit of political and economic integration (NEPAD and AU) and the increasing presence of emerging powers, especially China, but also the other BRICS countries and other strong developing nations. Based on new capital flows between the semi-periphery and periphery, a phenomenon linked to political-diplomatic and social initiatives from South-South Cooperation occurs and presents significant impacts on the transformation of the international system. Impacts strong enough to make the Western powers, as from the 2008 crisis, begin to seek the reversal of this process.